ANATOMICO-SURGICAL FOUNDATIONS OF DUODENOJEJUNAL CHANGE AT THE CHRONIC DUODENAL OBSTRUCTION - T. V. Timofeeva; V. K. Esipov; I. I. Kagan; K. V. Bachurin (Acta Biomedica Scientifica, 2012)
Anatomic and clinical research of duodenojejunal change in norm, and at the chronic duodenal obstruction, of functional character was realized. Peculiarities of motor-evacuation disorders + were revealed with help of X-ray method and peripheral computed, electrogastroenterography. Sizes, variants of forms of duodenojejunal change in norm, and in pathology were determined with, use of endoscopic method.